Time-on-market in Chinese condominium presales - Zhou, Xiaorong; Zahirovic-Herbert, Velma; Gibler, Karen M. (International Journal of Strategic Property Management, 2018)
The condominium presale market is characterized by information asymmetry between the developer and potential buyers. A condominium developer faces conflicting incentives to sell units quickly at a lower price to generate cash and sales momentum versus to hold prices high and endure longer marketing time to maximize revenues and maintain the property’s value. We examine the pattern of marketing duration for condominium units offered for presale in a large homogeneous development in Chengdu, China using a Cox proportional hazards model. Results indicate that a patient developer may extract a price premium on units. Diminishing risk to buyers is associated with shorter marketing duration. Time-on-market is also influenced by unit and building size as well as orientation. Market conditions may moderate the speed at which units are sold.